De la prensa literaria al libro: José María Vergara en la formación del hispanismo en Colombia (1858-1866) (Revista de Crítica Literaria Latinoamericana, 2015)
"This article examines the role that conservative editors, particularly José María Vergara (1831-1872), played in the formation of the literary field in Colombia during the decade of 1860. His work as editor and publisher facilitated the preservation of an important corpus of short narratives, still recognized as part of the nineteenth century literary canon of Colombia. The newly created editorial spaces for the rising number of Colombian writers sought to provide an opportunity for literary expression void of politics."
Keywords: Hispanism; Anthologies; Literary magazines; José María Vergara; Costumbrism; Female audiences